Behavioral Simulation of ISO 18000-6 Type-C Class 1 Gen2 Protocol for RFID UHF Transponder and its Application as Anti-collision Protocol in Interference Case - Saadi, Hadjer; Rnnane, Ahmed; Touhami, Rachida; C.E. Yagoub, Mustapha (International Journal of Engineering and Technology, 2018)
In RFID systems, the Transponder Protocol usually uses the standard ISO 18000-6 Type-C Class 1 Generation 2, originally developed to communicate with the reader. Since a typical RFID system could be used in a myriad of tasks from product identification to environmental sensing, behavioral software functionality and hardware cost constraints are extremely constricted, principally due to their ¶standard’s requirements.¶ Thus, in this paper, an advanced behavioral simulation of the Tag ID layer of ISO 18000-6 Type-C protocol is proposed with all its states, commands and functionality, a crucial step toward effective design and test. The approach was then successfully applied to collision issues in interference case.